Melatonin prevents blood vessel loss and neurological impairment induced by spinal cord injury in rats. (4th March 2017) - Jing, Yingli; Bai, Fan; Chen, Hui; Dong, Hao
Abstract : Background : Melatonin can be neuroprotective in models of neurological injury, but its effects on blood vessel loss and neurological impairment following spinal cord injury (SCI) are unclear. Our goal herein was to evaluate the possible protective action of melatonin on the above SCI-induced damage in rats. Materials and methods : Sixty-three female Sprague-Dawley rats were randomly divided into three equal groups: sham, SCI and melatonin groups. Melatonin (10 mg/kg) was injected intraperitoneally and further administered twice a day at indicated time after a moderate injury at T10 in melatonin group. Blood vessel was assessed by CD31staining and FITC-LEA, the permeability of blood–spinal cord barrier (BSCB) was detected by Evan's Blue. Neuron was assessed by NeuN staining and the expression of Nissl bodies in the neurons was assessed by Nissl staining. The expressions of brain-derived neurotrophic factor (BDNF), synapsin I, or growth associated protein-43 (GAP-43) in the spinal cord and hippocampus were evaluated by Western blotting. Results : At 7 days post-injury, melatonin treatment rescued blood vessels, increased CD31 levels, ameliorated BSCB permeability. Additionally, melatonin significantly increased the number of neurons and the expression of Nissl bodies in neurons at the injury epicenter. Furthermore, our data showed that SCI reduced levels of the molecular substrates of neurological plasticity, including BDNF, synapsin I, or GAP-43 in the spinal cord and hippocampus. Melatonin treatment partially prevented these reductions. Conclusion : The neuroprotective effect of melatonin was associated with melioration of the microcirculation in the spinal cord and reduction of neurological impairment in the spinal cord and brain.